Composición química de la biomasa residual de la planta de piña variedad MD2 proveniente de Guácimo, Limón - Irías, Andrea (2015)
Moisture content, lignin, holocellulose, nitrogen and mineral contents (potassium, calcium, iron, magnesium, sodium) were determined in the stover biomass, resulting from the harvesting of pineapple plant MD2 in February 2009 in the Guácimo region. The analytical methodology included solvent extraction, Kjeldahl digestion/titration and atomic absorption spectrometry. Differences were found in chemical composition between the material analized and those reported for other regions, which must be specified to ensure utilization of stover biomass and its proper fertilization for obtaining good yields, and preserving the integrity of the farming activity.